2003
DOI: 10.1081/cbi-120024218
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Aspects of Postprandial Metabolism

Abstract: Time-dependent variations in the hormonal and metabolic responses to food are of importance to human health, as postprandial metabolic responses have been implicated as risk factors in a number of major diseases, including cardiovascular disease. Early work reported decreasing glucose tolerance in the evening and at night with evidence for insulin resistance at night. Subsequently an endogenous circadian component, assessed in constant routine (CR), as well as an influence of sleep time, was described for gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 41 publications
2
62
1
4
Order By: Relevance
“…Our correlation data suggest that the differences in male and female sleep patterns may be related to sexspecific differences in metabolic needs (Montooth et al 2003;Morgan et al 2003;De Luca et al 2005). The relatively high genetic correlations that we observed between sleep and energy stores may reflect the fact that large metabolic changes occur with high probability with the introduction of single P-element insertions in flies, implying that large numbers of genes influence metabolism (Clark et al 1995).…”
mentioning
confidence: 65%
“…Our correlation data suggest that the differences in male and female sleep patterns may be related to sexspecific differences in metabolic needs (Montooth et al 2003;Morgan et al 2003;De Luca et al 2005). The relatively high genetic correlations that we observed between sleep and energy stores may reflect the fact that large metabolic changes occur with high probability with the introduction of single P-element insertions in flies, implying that large numbers of genes influence metabolism (Clark et al 1995).…”
mentioning
confidence: 65%
“…This diurnal change was evident at all levels of circulating glucose, although the amplitude was greater at higher glucose concentrations (Boden et al, 1996). Other investigators have also reported circadian variations in insulin sensitivity, glucose tolerance and postprandial metabolism (Lee et al, 1992;Morgan et al, 2003). Given the variety of study designs and the lack of meal standardization, the basis and magnitude of sequential effects deserves further investigation.…”
Section: Insulin Sensitivity Following Sequential Mealsmentioning
confidence: 99%
“…In humans, diurnal variations in glucose tolerance have long been described (18), and rhythmic profiles of plasma glucose, insulin, and triglycerides have been detected (19,20). Furthermore, a lipidomic analysis of human plasma has shown that ∼18% of all lipid profiles oscillate in a circadian manner independent of sleep and food intake (19).…”
Section: Significancementioning
confidence: 99%